Myositis ossificans in the diabetic foot: a review of the literature with an illustrative case series. Issue 12 (December 2019) - Sharma, Vivek; Sharma, Dhiraj; Dinar, Heather; Dhatariya, Ketan K
Objective: Myositis ossificans is a rare non-neoplastic form of heterotopic ossification most commonly described after trauma or surgery, in the diabetic foot. Design: We provide a review of the literature including three illustrative cases. Participants: Individuals presenting to the foot clinic. Setting: Single centre, tertiary multidisciplinary specialist diabetes foot clinic. Results: We review the literature surrounding Myositis ossificans, and describe three cases of Myositis ossificans following foot surgery in people with diabetes. All of the imaging was consistent with the descriptions of Myositis ossificans reported elsewhere in large muscle groups. These are the first reports of Myositis ossificans occurring in the feet of people with diabetes. Conclusions: Myositis ossificans has only very rarely been described in the foot and, as far as we are aware, never in people with diabetes. Given that the prevalence of diabetes is increasing, and the foot problems requiring surgery are also rising, we suggest that clinicians should be more aware of this condition because it may occur more frequently.